2023
DOI: 10.3390/buildings13020333
|View full text |Cite
|
Sign up to set email alerts
|

Development of Flash-Calcined Sediment and Blast Furnace Slag Ternary Binders

Abstract: Partial cement replacement by low-carbon-impact additions has the potential to reduce CO2 emissions. The aim of this study is the development of a ternary binder that includes ordinary Portland cement (OPC), ground granulated blast furnace slag (GGBS), and flash-calcined sediment (FCS). To upgrade dredged mineral material into FCS, a new heat treatment, i.e., flash calcination, was used. The used materials were physically, chemically, and mineralogically characterized. The mixture design method was used to opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Analyzing their physical and mechanical characteristics, they concluded that these new mixes comply with the specifications of the current Portland cement standards [5]. Zeraoui et al [6] prepared some ternary binders by mixing common Portland cement, ground granulated blast-furnace slag, and flash-calcined sediment. They found that the mix with 10% flash-calcined sediment and 40% ground granulated blast-furnace slag could replace 50% common Portland cement.…”
Section: Introductionmentioning
confidence: 96%
“…Analyzing their physical and mechanical characteristics, they concluded that these new mixes comply with the specifications of the current Portland cement standards [5]. Zeraoui et al [6] prepared some ternary binders by mixing common Portland cement, ground granulated blast-furnace slag, and flash-calcined sediment. They found that the mix with 10% flash-calcined sediment and 40% ground granulated blast-furnace slag could replace 50% common Portland cement.…”
Section: Introductionmentioning
confidence: 96%
“…The BET-specific surface area of CEM III SF is much higher than that of CEM III Ref. An increase in BET surface area could lead to an increase in water demand and the initial setting time of CEM III SF cement compared with the reference as indicated in previous studies [39,32,45] . The curve of particle size distribution of both cements is shown in Figure 4.…”
Section: Anhydrous Cements Characterizationmentioning
confidence: 84%
“…Although the use of flash-calcined sediment as a replacement for GBFS and metakaolin (MK) in cementitious materials was investigated in previous studies [39,40], the impacts of flash-calcined sediment substitution on the hydration kinetics, the formation of hydration products, and the potential change in the composition of hydrates were not studied. In addition, in these studies, the supplementary cementitious materials were directly mixed with the cement; this could lead to a potential change in the particle size distribution of blended cement, affecting the hydration and the development of mechanical-microstructural properties of mixtures.…”
Section: Significance and Originalitymentioning
confidence: 99%
“…In an attempt to produce low-carbon and cost-effective blended cements, new formulations are currently being investigated [ 34 ]. Zeraoui et al [ 35 ] studied ternary binders (Portland cement-ground granulated blast-furnace slag-flash-calcined sediment) and reported that 10% flash-calcined sediment plus 40% ground granulated blast-furnace slag can replace 50% of Portland cement. However, the water demand increases with the use of flash-calcined sediment, but it enhances the compactness and density of the mortar.…”
Section: Introductionmentioning
confidence: 99%